Experience of an NIHR Clinical Lectureship (medical/dental) and the determining factors for a clinical academic career post lectureship: a mixed-method evaluation - Emma Knowles; Lorraine Harper; Jenny Hewison; Peter Thompson; Matthew R Mulvey; James Fenton; Helen Harris-Joseph; Lisa Ann Cotterill; Kieran Lee; Chris James Stevenson; Hein Heuvelman; Clare McVicker; et al. (BMJ Open, 2023)
Objectives The objective of this study is to investigate early-to-late postdoctoral clinical academic progression and the experiences of NIHR Clinical Lectureship (CL) fellows, considering enablers and barriers to success, and identifying the factors associated with immediate progression to a clinical academic role following completion of the award.Setting Datasets of CL awardees across the UK.Participants For semistructured interviews, n=40 CL awardees that had finished their award within the previous 5 years. For quantitative analysis, n=1226 completed or currently active CL awardees.Outcome measures The responses from the semistructured interviews to the defined questions on experiences during the award, postaward progression, and enablers and barriers to academic progression. Other primary outcome measures were quantitative data on first destinations postaward, demographic data, and whether an awardee had previously held an NIHR Academic Clinical Fellowship (ACF) or was a recipient of the Academy of Medical Sciences (AMS) Starter Grant.Results CL awardees identified numerous benefits to the award, with the majority achieving their aims. Most awardees progressed to a clinical academic role; however, some returned to a clinical only position, citing concerns around the time pressure associated with balancing clinical and academic responsibilities, and the competition to attain further postdoctoral awards. The region of the award partnership, year of award end and success in applying for an AMS Starter Grant were associated with progression to a clinical academic role. Gender, holding an ACF and having a craft or non-craft specialty had no independent statistical association with clinical academic progression.Conclusions The CL is a valued element of the Integrated Academic Pathway. By addressing issues around later postdoctoral progression opportunities, responding to challenges experienced by CLs, and by understanding the factors identified in this study associated with clinical academic progression, it should be possible to increase the proportion of CLs that become fully independent clinical academic research leaders.Participants 1226 NIHR CLs active or completed on the award between 2006 and 2020.